Spartakiada z okazji X-lecia Z. S. "Start". (Bytom : [s.n.], 1963)
Afisz inf. o zawodach 4-6.10.1963 r.
Keywords: Sport -- Polska -- 1945-1970 -- druki ulotne; Bytom (Polska) -- 1945-1970 -- druki ulotne